2014
DOI: 10.4162/nrp.2014.8.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adipocytokines and antioxidants-status in Korean overweight and obese females with dyslipidemia

Abstract: BACKGROUD/OBEJECTIVESIt is hypothesized that obese people with dyslipidemia is more likely to have increased oxidative stress and decreased antioxidant status, in comparison with the controls who were obese without dyslipidemia. Thus, the aims of the present study were to determine the dietary intakes, plasma adipokines, and antioxidative systems between obese with dyslipidemia and obese without dyslipidemia were investigated.SUBJECTS/METHODSFemale subjects who were between 20 and 55 years old, and whose BMI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
1
0
2
Order By: Relevance
“…However, in this study there was a significant decrease in TAC in relation to BMI. This is in line with Kelly et al (28) who reported a significant decrease in TAC among obese children with multimetabolic syndrome, this agrees with the findings of Wha Ha et al (29).…”
Section: Discussionsupporting
confidence: 93%
“…However, in this study there was a significant decrease in TAC in relation to BMI. This is in line with Kelly et al (28) who reported a significant decrease in TAC among obese children with multimetabolic syndrome, this agrees with the findings of Wha Ha et al (29).…”
Section: Discussionsupporting
confidence: 93%
“…36 Oxidative stress is due to an imbalance between increased ROS levels and host antioxidant defenses, resulting in cell damage. [37][38][39] The TAC is a measure of the combination of endogenous and exogenous antioxidant molecules in extracellular fluids, and it has been studied in both plasma and saliva in relation to pathological status. [40][41][42][43][44] Specifically, TAC assay has been studied to characterize the pathologic state in the saliva of pregnant women with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hay más información disponible en niños japoneses de edad escolar, en hombres y mujeres de Nepal con un rango etario entre 10 y 68 años, en mujeres mexicanas entre 30 y 45 años, en niños filipinos de edad escolar, en mujeres coreanas entre 20 y 55 años, en hombres y mujeres entre 46 y 67 años, en mujeres en edad fértil y embarazadas entre 25 y 35 años, en niños chinos escolares 67,70,[76][77][78][79][80][81] .…”
Section: Relación Entre Estado Nutricional Y Vitaminas Liposolublesunclassified
“…Sin embargo, la vitamina E ajustada a lípidos no tuvo asociación con ningún indicador antropométrico. Si comparamos con mujeres coreanas, con IMC ≥ 23 kg/m 2 , dislipémicas, tuvieron menores niveles de α-tocoferol/CT y retinol/CT 79 . En un estudio de 276 mujeres de 46-67 años se encontró una media de IMC de 25,4 ± 0,2 kg/m 2 , %MG de 31,6 ± 0,3, CC de 77,9 ± 0,7 cm (todos los valores un poco más bajos que en nuestro estudio).…”
Section: (Cm)unclassified